Time to eat reveals the hierarchy of peripheral clocks. Issue 11 (November 2021) - Zhang, Zhihui; Shui, Guanghou; Li, Min-Dian
Abstract : Meal timing resets trillions of cellular circadian clocks in the body. Recent advances in multiomics demonstrate that clocks in peripheral tissues are differentially reset by feeding rhythm, and modulated by the central clock and the liver clock. This highlights the essential roles of tissue-specific regulation and intercellular signaling in clock synchronization.